An Extremely Rare SRD5A2 Gene c.485A>C Mutation in a Compound Heterozygous Newborn with Disorders of Sex Development First Identified in Vietnam - Phan Tuong Quynh Le; Thanh Nha Uyen Le; Thi Thanh Binh Nguyen; Minh Thao Nguyen; Thi Minh Thi Ha (Case Reports in Endocrinology)
SRD5A2 (steroid 5-alpha-reductase 2) mutation, which impairs 5α-reductase-2 enzyme activity, is among the causes of 46,XY disorders of sex development (DSD). Here, we report a rare pathogenic mutation NM_000348.4:c.485A>C (NP_000339.2:p.His162Pro) of SRD5A2 gene in a compound heterozygous state first identified in a Vietnamese newborn with 5α-reductase-2 enzyme deficiency. We also first submitted this rare mutation to ClinVar database (VCV000973099.1). The patient presented with hyperpigmented labia-majora-like bifid scrotum, clitoris-like phallus, perineoscrotal hypospadias, and blind-ending vagina. The other mutation NM_000348.4:c.680G>A (NP_000339.2:p.Arg227Gln) was reported previously. This compound heterozygous mutation was first detected by next-generation sequencing. By Sanger sequencing, we confirmed that the c.485A>C mutation was maternal inherited, whereas the c.680G>A mutation was paternal inherited. Up to date, this is the first report of this rare compound heterozygous state of SRD5A2 c.485A>C and c.680G>A mutations in patients with 46,XY DSD generally as well as in Vietnamese population particularly and is also the second report in the world carrying the pathogenic mutation NM_000348.4:c.485A>C (NP_000339.2:p.His162Pro). Our finding has enriched the understanding of the spectrum of SRD5A2 variants and phenotypic correlation in Asian patients with 46,XY DSD.